Follow-Up of Intracranial Aneurysms Selectively Treated with Coils: Prospective Evaluation of Contrast-Enhanced MR Angiography - Pierot, L.; Delcourt, C.; Bouquigny, F.; Breidt, D.; Feuillet, B.; Lanoix, O.; Gallas, S. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: The aim of this study was to determine the feasibility and usefulness of contrast-enhanced MR angiography (CE-MRA) for the follow-up of intracranial aneurysms treated with detachable coils, by comparing CE-MRA with digital subtraction angiography (DSA) and 3D time-of- flight (TOF) MRA.METHODS: Thirty-two patients with 42 treated aneurysms were included in the study; 6 had been treated for multiple aneurysms. All MRAs were performed with a 1.5T unit within 48 hours of DSA. We performed 2 types of acquisition: a 3D TOF sequence and CE-MRA. Twenty-eight patients were included 1 year after endovascular treatment, and 4 patients, after 3 years or more. DSA was the technique of reference for the detection of a residual neck or residual aneurysm.RESULTS: Compared with DSA, the sensitivity of MRA was good. For the detection of residual neck, there was no significant difference between the results of 3D TOF MRA (sensitivity, 75%–87.5%; specificity, 92.9%, according to both readers) and CE-MRA (sensitivity, 75%–82.1%; specificity, 85.7%–92.9%). For the detection of residual aneurysm, sensitivity and specificity of both techniques were the same, respectively 80%–100% and 97.3%–100%. Therefore, CE-MRA was not better than 3D TOF MRA for the detection of residual neck or residual aneurysm. For large treated aneurysms, there was no difference between decisions regarding further therapy after CE and 3D TOF MRA, even though CE-MRA with a short echotime and enhancement gave fewer artifacts and better visualization of recanalization than 3D TOF MRA. The interpretation of transverse source images and the detection of coil mesh packing seemed easier with 3D TOF imaging.CONCLUSION: This prospective study did not show that CE-MRA was significantly better than 3D TOF MRA for depicting aneurysm or neck remnants after selective endovascular treatment using coils. For aneurysms treated with coils, 3D TOF MRA seems a valid and useful technique for the follow-up of coiled aneurysms.